2019
DOI: 10.1177/0883911519835569
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and biodegradation properties of polycaprolactone/polydioxanone composite scaffolds prepared by blend or co-electrospinning

Abstract: Electrospun polymer scaffolds are regarded as an ideal tissue engineering scaffold due to similar morphological properties with the native extracellular matrix. Among these, polycaprolactone is widely used to fabricate electrospun fibrous scaffolds due to its excellent biocompatibility, good mechanical properties, and ease of manufacture. However, its low biodegradation rate has a negative influence on its application in tissue engineering scaffold. To address this issue, this study prepared hybrid scaffolds c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Polydioxanone (PDO) is widely used for clinical bioabsorbable sutures because its biocompatibility enables cell adhesion and infiltration [15][16][17][18]. PDO monofilaments have been used to create a mesh-type stent [19], which has been employed in pediatric patients with airway problems.…”
Section: Introductionmentioning
confidence: 99%
“…Polydioxanone (PDO) is widely used for clinical bioabsorbable sutures because its biocompatibility enables cell adhesion and infiltration [15][16][17][18]. PDO monofilaments have been used to create a mesh-type stent [19], which has been employed in pediatric patients with airway problems.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is a challenge for blending electrospinning of two polymers with low compatibility. Thus, co‐electrospinning is considered as an alternative technique, which employs multiple spinnerets in the electrospinning setup and allows the fibers simultaneously deposited onto the same collector (Figure 3j) (Zhou et al., ). Zander, Orlicki, Rawlett, and Beebe () produced the bicomponent fiber mats by co‐electrospinning of PCL with PEO, and found that the porosity of the fiber mats could be tailored by the amount of PEO, and the nanoscale size and high surface area of the PCL electrospun fibers were not affected by the varied porosity.…”
Section: Design Of Electrospinningmentioning
confidence: 99%
“…The in vitro biodegradation study aims to investigate the biodegradation rate of prepared scaffolds [35]. Briefly, each scaffold (n = 3) with known weight (W 0 ) was incubated at 37degC in alpha-MEM culture media containing 1% (v/v) penicillin/streptomycin to prevent bacterial growth.…”
Section: In Vitro Biodegradation Studymentioning
confidence: 99%
“…Details on the physicochemical characterization of the GO powder used as well as of the obtained rGO scaffolds were published elsewhere. [ 35 ] Numerous studies showed that coating reagents such as poly-l-lysine (PLL) and laminin (LAM) on the surface of the scaffolds induce signals regulating cell responses, adhesion and growth [19]. However, it is interesting to point out that various coating reagents have different impacts on cellular behaviour according to scaffold biomaterial and cell type [20].…”
Section: Introductionmentioning
confidence: 99%